Terror as a Bargaining Instrument : A Case Study of Dowry Violence in Rural India - Rao, Vijayendra 1984- (The World Bank, 1999)
May 2000 - Some aspects of violent behavior are linked to economic incentives and deserve more attention from economists. In India, for example, domestic violence is used as a bargaining instrument, to extract larger dowries from a wife's family, after the marriage has taken place. Bloch and Rao examine how domestic violence may be used as a bargaining instrument, to extract larger dowries from a spouse's family. The phrase dowry violence refers not to the dowry paid at the time of the wedding, but to additional payments demanded by the groom's family after the marriage. The additional dowry is often paid to stop the husband from systematically beating the wife. Bloch and Rao base their case study of three villages in southern India on qualitative and survey data. Based on the ethnographic evidence, they develop a noncooper-ative bargaining and signaling model of dowries and domestic violence. They test the predictions from those models on survey data. They find that women whose families pay smaller dowries suffer increased risk of marital violence. So do women who come from richer families (from whom resources can more easily be extracted). Larger dowries - as well as greater satisfaction with the marriage (in the form of more male children) - reduce the probability of violence. In India marriage is almost never a matter of choice for women, but is driven almost entirely by social norms and parental preferences. Providing opportunities for women outside of marriage and the marriage market would significantly improve their well-being by allowing them to leave an abusive husband, or find a way of bribing him to stop the abuse, or present a credible threat, which has the same effect. This paper - a product of Poverty and Human Resources, Development Research Group - is part of a larger effort in the group to examine crime and violence in developing countries. Vijayendra Rao may be contacted at vrao@worldbank.org